The linked employer-employee study of the socio-economic panel (SOEP-LEE): Project report - Michael Weinhardt; Alexia Meyermann; Stefan Liebig; Jürgen Schupp (Deutsches Institut für Wirtschaftsforschung (DIW), 2016)
In 2012/13, a survey of German employers was conducted using face-to-face and paper-and-pencil interviews (N = 1,708; response rate = 30.1%). Establishments were sampled based on address information provided by employed participants in the Socio-Economic Panel (SOEP) study. The information obtained from both surveys can be linked in order to create a linked employer-employee data set concerning organizational strategies and labor market outcomes (N = 1,834). Paradata were collected regarding several aspects of the survey: contact forms informed about the fieldwork process; an interviewer survey provided information about the interviewer staff; every interview situation was evaluated separately by interviewers to learn more about the response process in establishments; the editing process was reassessed; and 31 interviews were audiotaped to gain insights into the interviewing process. This project report covers the design of the study, the data collection stage, and field outcomes. It evaluates the establishment survey itself, as well as the linked SOEP-LEE data set, by looking at selectivity in nonresponse and at measurement errors overall. The establishment data and the linked SOEP-LEE data are available for secondary use at the research data centers of the SOEP at DIW Berlin and at the Data Service Center for Business and Organizational Data (DSC-BO) at Bielefeld University (DOI:10.7478/s0549.1.v1).
Keywords: 330